Nature-based activities and mental well-being in adults: a study on perceived health outcomes - Bilal Okudan; Ozkan Isik; Ozkan Isik; Rifat Yagmur; Canan Bastik Salkim; Laurentiu-Gabriel Talaghir; Teodora Mihaela Iconomescu (Frontiers in Public Health)
BackgroundNowadays, nature-based sports activities stand out as an essential factor that positively affects individuals’ psychological well-being beyond supporting their physical health. Physical activities in the natural environment can support individuals’ mental well-being by reducing their stress levels, increasing their life satisfaction, and strengthening their psychological resilience. Accordingly, this study aimed to examine the effect of perceived health outcomes from nature-based sport activities on adults’ mental well-being.MethodA relational screening model was employed with 350 adult participants (183 male, 167 female) engaged in nature-based sports such as skiing, snowboarding, mountaineering, and paragliding in Kocaeli, Türkiye. Participants were selected using a convenience sampling method. Data were collected through a personal information form, the Perceived Health Outcomes of Recreation Scale, and the Mental Well-Being Scale. Both scales demonstrated high reliability in this study (Cronbach’s α = 0.93–0.94 for health outcomes; α = 0.93 for mental well-being). Normality was verified through skewness and kurtosis values. Data analysis included descriptive statistics, correlation, regression, cluster, and univariate analyses conducted using SPSS 23.ResultsIt was determined that there was a positive relationship between perceived health outcomes and mental well-being. In addition, it was observed that perceived health outcomes have a positive effect on mental well-being and predicted mental well-being by approximately 24%. In particular, it was determined that adults who regularly participate in nature-based sports have higher levels of mental well-being in groups with high levels of perceived health outcomes.ConclusionIt can be stated that regular participation in nature sports creates a positive effect on mental well-being by increasing the level of perceived health outcomes. It can be stated that regular participation in nature sports creates a positive effect on mental well-being by increasing the level of perceived health outcomes. Therefore, promoting accessible and inclusive nature-based sports programs in communities, workplaces, and educational settings is recommended to support public mental and physical health.